Web Performance Engineering - Finding Best Data Structure For Automatically Collected HTML Locators - Padhy, Prabhat; Nayak, Pratima; Vaidya, Siddhesh (2023 2nd International Conference on Computational Systems and Communication (ICCSC), 2023)
The research basically aims to identify finding the best Data Structure and automatic detection of locators. This in turn leads to tracking (navigating) for the URL and its content. The term "Locators" can be described as an address that identifies a web element uniquely that is no repeatable within the webpage, It's a command that informs Selenium Integrated Development Environment which Graphical User Interface elements like - Text Box, Buttons, Check Boxes etc, it needs to operate on. Detecting correct GUI elements is a prior work for generating an automation script but, precise identification of GUI elements is much more difficult. Sometimes, you might even end up working with incorrect GUI elements or no elements at all, therefore, using the right locator ensures that the tests are faster, more reliable, or has lower maintenance over releases.